Surgical treatment of varicose veins and venous malformations in Klippel–Trenaunay syndrome. (April 2016) - Malgor, Rafael D; Gloviczki, Peter; Fahrni, Jennifer; Kalra, Manju; Duncan, Audra A; Oderich, Gustavo S; Vrtiska, Terri; Driscoll, David
Background: Klippel–Trenaunay syndrome (KTS) is a mixed mesenchymal malformation characterised by varicose veins, venous and capillary malformations, and hypertrophy of soft tissue and bone. The purpose of this study was to evaluate the surgical outcomes in KTS patients to provide standards for comparison with endovenous therapy. Methods: The clinical data of consecutive patient with KTS who underwent open venous surgical treatment between January 1987 and December 2008 were reviewed. Demographics, clinical presentation, operative data, and clinical outcomes were recorded. Follow-up information was obtained from the medical records, mailed questionnaires and phone calls. Descriptive statistics, the Kaplan–Meier method and Log-rank statistics were used where appropriate. Results: Twenty-seven females and 22 males, (mean age 26.5 years, range 7.7–55.8) were included in this study. All had varicose veins, 36 (73%) had limb hypertrophy, and 33 (67%) had capillary malformations, with two of three clinical features present in all. The most frequent symptom was pain (N = 43, 88%). Forty-nine patients underwent operations on 53 limbs. Stripping of the GSV, small and accessory saphenous and lateral embryonic veins was performed in 17 (32%), 10 (19%), 9 (17%), and 15 (28%) limbs, respectively. Two patients developed deep vein thrombosis, one had pulmonary embolism (PE), and one patient had peroneal nerve palsy. Freedom from disabling pain at 1, 3 and 5 years was 95%, 77% and 59%, respectively, and freedom from secondary procedures was 78% at 3 years, and 74% at 5 years. At the last follow-up visit, the venous clinical severity score had decreased from 9.48 ± 3.27 to 6.07 ± 3.20 (P < 0.001). Conclusions: In selected symptomatic patients with KT syndrome, open surgical treatment is safe and durable. Three-fourths of the patients remain free of disabling pain at five years, but secondary procedures are required in one-fourth of the patients. These data can serve as standards for comparison of endovenous therapy for KT syndrome.